1978
DOI: 10.1071/bi9780373
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Intravenously Infused Dexamethasone in Sheep

Abstract: Aust. J. Bioi. Sci., 1978, 31, 373-83 The metabolism of [1,2(n)-3Hldexamethasone intravenously infused for periods of 4 and S days was examined in four Merino wethers.On average 85·6±2·8 (s.e.m.) % of the total dose was recovered, 56·2±5·1 and 29·4±3·3% being excreted in urine and faeces respectively. In total 12·4 % of the dose was associated with the unconjugated steroid fraction which represented 22% of the total urinary radioactivity.Thin layer chromatography of the urinary unconjugated fractlon reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The dexamethasone concentration profiles revealed a pattern which reflects the extensive dexamethasone metabolism as shown by Leish and Panaretto (1978). Also, the fall in the wet skin weight per unit area confirmed previous observations in sheep (Panaretto, unpublished data) and studies in rats (Young et al 1977;Cutroneo and Counts 1975) in which the similar weight loss has been shown on drying the dexamethasone-treated wet skin to constant weight.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The dexamethasone concentration profiles revealed a pattern which reflects the extensive dexamethasone metabolism as shown by Leish and Panaretto (1978). Also, the fall in the wet skin weight per unit area confirmed previous observations in sheep (Panaretto, unpublished data) and studies in rats (Young et al 1977;Cutroneo and Counts 1975) in which the similar weight loss has been shown on drying the dexamethasone-treated wet skin to constant weight.…”
Section: Discussionsupporting
confidence: 77%
“…Administration of several glucocorticoids to sheep and the resultant inhibition of growth of wool fibres have been well documented (Panaretto and Wallace 1978a, 1978b, 1979Leish and Panaretto 1978). In ,order to induce shedding of the majority of wool fibres, it was found necessary to maintain elevated glucocorticoid concentrations in the plasma of sheep over 8 days or longer (Panaretto 1979).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration profiles for dexamethasone here were similar to those of Panaretto and Wallace (1978b). Leish and Panaretto (1978) reported similar concentration patterns using [3H]dexamethasone. The peaks in steroid concentration have not been investigated here.…”
Section: Discussionsupporting
confidence: 69%
“…Dexamethasone quickly disappeared from the circulation on cessation of the infusion (Leish and Panaretto 1978) and by 45 days after treatment wool growth was almost restored. to normal.…”
Section: Discussionmentioning
confidence: 99%
“…Previous papers have described some effects of different forms of dexamethasone (Panaretto et al 1975;Panaretto and Wallace 1978a; Leish and Panaretto 1978) and flumethasone Wallace 1978b, 1979) on wool growth in Merino sheep. The results have shown that these steroids induce fibre shedding.…”
Section: Introductionmentioning
confidence: 99%